INCIDENCE AND SEVERITY OF ACUTE MOUNTAIN SICKNESS AND ASSOCIATED SYMPTOMS IN TAIWANESE CHILDREN ON XUE MOUNTAIN (3, 886 M). Issue 12 (18th November 2016) - Cheng, F
Abstract : Objectives & Background: Acute mountain sickness (AMS) is common among people who trek at high altitudes. Headache, the cardinal symptom of AMS, is often accompanied by dizziness, fatigue, nausea and vomiting, and sleep disturbances. The incidence of AMS in children varies, and large group population studies in children are rare. We examined the incidence of AMS and prevalence of AMS-associated symptoms in older children trekking Xue Mountain in Taiwan. Methods: This prospective cohort study included 197 healthy, non-acclimatized 11 and 12-year-old children who participated in a round-trip trek from the trailhead to the summit of Xue Mountain (2, 179 m to 3, 886 m) over 3 days. We used the Lake Louise AMS scoring criteria to record daily AMS-associated symptoms (headache, dizziness, fatigue, anorexia, vomiting, and sleep disturbances) and to diagnose AMS. Medication was prescribed at the onset of AMS symptoms. Written informed consent was obtained from all of the subjects and their parents. Results: The overall incidence of AMS was 40.6%. The incidence was higher in males and in children with a higher body mass index ( p <0.05). Previous high altitude experience, AMS history, and menstruation were not associated with the development of AMS. The mean overall AMS score of was 1.77±2.08. The mean AMS score of subjects developed AMS (3.02±2.46) was significantly higher than that of those in the non-AMS group (0.92±1.16, p <0.001). The most common symptom was sleep disturbance followed by dizziness, and headache. The prevalence of headache was 46.2% on Day 2 at 3, 100 m, and 31.3% on Day 3 at the same altitude. Males experienced significantly more headache and fatigue during the trip ( p <0.05). The AMS scores and prevalence of all the AMS symptoms were significantly higher in the AMS than in the non-AMS group ( p <0.05). Conclusion: Although AMS was common among the participants in our study, the symptoms were mild in most cases. Sleep disturbance was the most common symptom. The effects of medication or acclimatization may explain the lower incidence of headache on Day 3 compared to Day 2. The incidence of AMS in our study was higher than that previously reported in adults, and lower than that of a previous study on Jade Mountain (3, 952 m) in Taiwan.Figure 1 Figure 2 Figure 3